Use of touch screen tablets to support social connections and reduce responsive behaviours among people with dementia in care settings: a scoping review protocol. Issue 11 (19th November 2019) - Hung, Lillian; Berndt, Annette; Wallsworth, Christine; Horne, Neil; Gregorio, Mario; Mann, Jim; Son, Cathy; Camps, Ainsley; Chow, Bryan; O'Neill, Ryan; Chaudhury, Habib
Abstract : Introduction: The disabilities associated with dementia make the adjustment to staying in a care setting stressful. Separation from family can exacerbate the effects of stress. The use of touch screen tablets such as an iPad may offer potential to support the person with dementia staying in a care setting. Although electronic devices are used among people with dementia for a variety of purposes, a comprehensive review of studies focusing on their impact in care settings for social connection and patient/resident behaviour is lacking. This scoping review will focus on the use of touch screen tablets to support social connections and reducing responsive behaviours of people with dementia while in a care setting, such as a hospital ward. Methods and analysis: This scoping review will follow Joanna Briggs Institute scoping review methodology. The review team consists of two patient partners and three family partners, a nurse researcher, a research assistant and an academic professor. All authors including patient and family partners were involved in preparing this scoping review protocol. In the scoping review, we will search the following databases: MEDLINE, AgeLine, Cochrane, CINAHL, PsycINFO and IEEE. Google and Google Scholar will be used to search for additional literature. A hand search will be conducted using the reference lists of included studies to identify additional relevant articles. Included studies must report on the impact of using a touch screen technology intervention that involves older adults with dementia in care settings, published in English since 2009. Ethics and dissemination: This review study does not require ethics approval. By examining the current state of using touch screen tablets to support older people with dementia in care settings, this scoping review can offer useful insight into users' needs (eg, patients' and care providers' needs) and inform future research and practice. We will share the scoping review results through conference presentations and an open access publication in a peer-reviewed journal.